Positive electrode material, preparation method thereof and lithium ion battery
By adopting a cobalt-free cathode material with a core-clad layer structure, Li2Ni2TeO6 and LaB6 caps are used to improve the performance of lithium-ion batteries, and the problems of reduced battery capacity and poor rate performance caused by cobalt-free cathode material are solved.
Patent Information
- Application Number
- CN202211541583.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-12-02
AI Technical Summary
The existing cobalt-free positive electrode materials lead to problems such as reduced battery capacity and poor rate performance.
A double-layer structure positive electrode material of a core layer-clad layer is used. The core layer is a cobalt-free layered positive electrode material. The cladding layer includes Li2Ni2TeO6 and LaB6. It is prepared by calcining precursors and doping elements oxides and other materials.
The coating layer isolates the direct contact between the electrolyte and the core layer, reduces side reactions, improves lithium ion mobility and ion conductivity, improves the charge and discharge performance of large currents, and reduces residual alkali and stabilizes the slurry.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] As the core of lithium-ion batteries, the quality of positive electrode materials directly determines the performance of batteries. Nickel-cobalt-manganese (NCM) ternary positive electrode materials have become important positive electrode active materials for current power lithium-ion batteries, and NCM523, NCM622, NCM811, etc. have been commercialized on a large scale. However, due to the scarcity of international cobalt resources, low-cobalt or cobalt-free batteries have become a trend. However, for layered positive electrode materials, the lack of cobalt will inevitably result in poor material conductivity, reduced battery capacity, and poor rate performance. In addition, cobalt-free materials will have high residual alkali and unstable slurry. Summary of the invention
[0003] The embodiments of the present application provide a positive electrode material, a preparation method thereof and a lithium-ion battery, which can solve the problems of reduced battery capacity and poor rate performance caused by existing cobalt-free positive electrode materials.
[0004] The first aspect of the present application provides a positive electrode material, comprising a core layer and a coating layer arranged on the surface of the core layer; the general formula of the core layer includes LiNi x Mn y Me z O2, wherein 0.5<x<1, x+y+z=1, and Me is selected from at least one of Zr, Sr, W, Al, Ti, Mg, Ce, Y, and B elements; and the coating layer includes Li2Ni2TeO6 and LaB6.
[0005] Optionally, the positive electrode material is a layered positive electrode material, and the median particle size D50 of the positive electrode material is 2 to 4 μm.
[0006] Optionally, the specific surface area of the positive electrode material is 0.3 to 0.8 g / cm 2 The tap density of the positive electrode material is 1.6 to 2.0 g / ml.
[0007] The second aspect of the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0008] Provide a precursor, the molecular formula of which includes Ni a Mn b (OH)2, where 0.5<a<1, a+b=1;
[0009] The oxide Me containing the doping element Me m O n , lithium salt and the precursor are mixed and calcined to obtain a core layer;
[0010] The core layer is crushed and sieved, a nickel source and a tellurium source are added, and LaB6 is added, and the mixture is mixed and calcined to obtain the positive electrode material.
[0011] Optionally, the oxide of the doping element Me m O n The molar ratio of Me in the lithium salt, Li in the lithium salt and the sum of the amounts of metal elements Ni and Mn in the precursor is Me:Li:(Ni+Mn)=(0.002-0.006):(1.05-1.25):1.
[0012] Optionally, the median particle size D50 of the precursor is 2.5 μm to 4.5 μm, and the specific surface area is 10 g / cm 2 ~25g / cm 2 , the tap density is 1.2g / ml~2.0g / ml.
[0013] Optionally, an oxide Me doped with the element Me m O n The median particle size D50 is ≤50 nm, and the molar ratio of the lithium element in the lithium salt to the sum of the amounts of nickel and manganese in the precursor is 1.05≤Li / (Ni+Mn)≤1.25.
[0014] Optionally, the nickel source is nickel oxide; the tellurium source is tellurium dioxide; the median particle size D50 of the nickel source is ≤100nm, the median particle size D50 of the tellurium source is ≤100nm, and the median particle size D50 of LaB6 is ≤100nm; the mass of LaB6 is the oxide of the doping element Me m O n , lithium salt and precursor total mass 0.1% to 0.5%; the Me m O n wherein m is 1 or 2 or 3, n is 1 or 2 or 3, and Me m O n At least one selected from Al2O3, B2O3, ZrO2, TiO2, WO3, SrO, MgO, CeO2, and Y2O3.
[0015] Optionally, the full alkali of the core layer is tested, and the addition amount of the nickel source and the tellurium source is calculated according to the full alkali test result. The full alkali test method of the core layer comprises the following steps:
[0016] The core layer is dispersed in deionized water, stirred and filtered to obtain a supernatant, and the supernatant is titrated, using phenolphthalein and methyl orange as indicators of the titration end point, respectively, to obtain two titration end points, and the content a of LiOH and the content b of Li2CO3 are calculated;
[0017] The mass ratio of the core layer mass, the nickel source addition amount and the tellurium source addition amount is:
[0018] Core layer quality: nickel source addition amount: tellurium source addition amount = 1: [(a / 23.95+b / 73.87)×74.7]:
[0019] A third aspect of the present application provides a lithium-ion battery, comprising the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0020] The beneficial effect of the present application is to provide a positive electrode material, a preparation method thereof and a lithium ion battery having the positive electrode material. The structure of the positive electrode material is a double-layer structure of a core layer and a coating layer. The core layer is a cobalt-free layered positive electrode material. The Li2Ni2TeO6 in the coating layer can isolate the direct contact between the electrolyte and the core layer, which greatly reduces a series of side reactions. Moreover, the coating layer can improve the lithium ion migration ability and ion conductivity of the interface of the cobalt-free layered positive electrode material, thereby improving the large current charge and discharge performance of the positive electrode material. While synthesizing the Li2Ni2TeO6 coating layer, the lithium salt remaining on the surface of the cobalt-free layered positive electrode material is also consumed, so that the residual alkali is reduced and the slurry tends to be stable. The addition of LaB6 in the coating layer can improve the conductivity of the cobalt-free layered positive electrode material. LaB6 and Li2Ni2TeO6 jointly reduce the low-temperature DCR performance of the cobalt-free layered positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is a scanning electron microscope image of the positive electrode material provided in the examples of the present application. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0024] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of."
[0025] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0026] The embodiment of the present application provides a positive electrode material and a preparation method thereof, wherein the structure of the positive electrode material is a double-layer structure of a core layer and a coating layer, wherein the core layer is a cobalt-free layered positive electrode material, and the Li2Ni2TeO6 in the coating layer can isolate the direct contact between the electrolyte and the core layer, thereby greatly reducing a series of side reactions, and the coating layer can improve the lithium ion migration ability and ion conductivity of the interface of the cobalt-free layered positive electrode material, thereby improving the high-current charge and discharge performance of the positive electrode material, and while synthesizing the Li2Ni2TeO6 coating layer, the lithium salt remaining on the surface of the cobalt-free layered positive electrode material is also consumed, so that the residual alkali is reduced, and the slurry tends to be stable, and the addition of LaB6 in the coating layer can improve the conductivity of the cobalt-free layered positive electrode material, and LaB6 and Li2Ni2TeO6 jointly reduce the low-temperature DCR performance of the cobalt-free layered positive electrode material. As a typical application, the positive electrode material can be used to make lithium-ion batteries, and the lithium-ion batteries can be used in electric vehicles to provide electrical energy to power devices or energy storage devices.
[0027] In one embodiment of the present application, a positive electrode material is provided.
[0028] In some embodiments, Figure 1 As shown, the positive electrode material includes a core layer and a coating layer arranged on the surface of the core layer.
[0029] In some embodiments, the core layer is a cobalt-free layered positive electrode material, and the general formula of the core layer includes LiNi x Mn y Me zO2, 0.5<x<1, x+y+z=1, wherein the value of x can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range consisting of any two of them. Me is selected from at least one of Zr, Sr, W, Al, Ti, Mg, Ce, Y and B, preferably Zr.
[0030] The coating layer includes Li2Ni2TeO6. The Li2Ni2TeO6 coating layer is a nano-ion coating layer, which can isolate the direct contact between the electrolyte and the core layer, greatly reducing a series of side reactions, such as reducing the precipitation of transition metals, forming a thinner SEI film, reducing the precipitation of oxygen atoms, etc., thereby improving the electrochemical stability. In addition, Li2Ni2TeO6, as a fast ion conductor coating layer, can improve the lithium ion migration ability and ion conductivity of the positive electrode material interface, thereby improving the high current charge and discharge performance of the positive electrode material. In addition, while synthesizing the Li2Ni2TeO6 coating layer, the lithium salt remaining on the surface of the core layer is consumed, so that the residual alkali is reduced, the slurry tends to be stable, and the performance of the positive electrode active material layer formed by coating on the surface of the positive electrode current collector is stable.
[0031] In some embodiments, the coating layer further includes LaB6, which, as an electronic conductor, can improve the conductivity of the coating layer and cooperate with Li2Ni2TeO6 to reduce the low-temperature DCR performance of the positive electrode material.
[0032] In some embodiments, the median particle size D50 of the positive electrode material is 2.0 μm to 4.0 μm. Specifically, the median particle size of the positive electrode material can be 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4.0 μm or a range consisting of any two numbers therein. When the median particle size of the positive electrode material is within the above range, the particle size of the positive electrode material can be controlled within a reasonable range, reducing the side reaction between the positive electrode material and the electrolyte, while improving the cycle performance and rate performance of the lithium-ion battery.
[0033] In some embodiments, the specific surface area of the positive electrode material is 0.4 to 0.9 g / cm 2 Specifically, the specific surface area of the positive electrode material can be 0.4 g / cm 2 , 0.5g / cm 2 , 0.6g / cm 2 , 0.7g / cm 2 , 0.8g / cm 2 , 0.9g / cm 2Or a range consisting of any two of them. When the specific surface area of the positive electrode material is within the above range, the positive electrode material can be fully contacted with the electrolyte, providing a smooth channel for lithium ion insertion and extraction during the charging and discharging process of the lithium ion battery, shortening the lithium ion diffusion path, and improving the cycle life of the lithium ion battery.
[0034] In some embodiments, the tap density of the positive electrode material is 1.4 to 2.0 g / ml. Specifically, the tap density of the positive electrode material can be 1.4 g / ml, 1.5 g / ml, 1.6 g / ml, 1.7 g / ml, 1.8 g / ml, 1.9 g / ml, 2.0 g / ml, or a range consisting of any two numbers therein. When the tap density of the positive electrode material is within the above range, the lithium-ion battery has a higher gram capacity.
[0035] In some embodiments, a method for preparing a positive electrode material comprises the following steps:
[0036] S1) provides a precursor, the molecular formula of which includes Ni a Mn b (OH)2, wherein 0.5<a<1, a+b=1, wherein the value of a can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range consisting of any two numbers therein.
[0037] In some embodiments, the median particle size D50 of the precursor is between 2.5 μm and 4.5 μm. Specifically, the value of D50 can be 2.5 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm or a range consisting of any two numbers therein.
[0038] In some embodiments, the specific surface area of the precursor is 10m 2 / g~25m 2 / g, specifically, the value of the specific surface area can be 10m 2 / g, 12m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 25m 2 / g or a range consisting of any two numbers.
[0039] In some embodiments, the tap density of the precursor is between 1.2 g / ml and 2.0 g / ml. Specifically, the tap density can be 1.2 g / ml, 1.3 g / ml, 1.4 g / ml, 1.5 g / ml, 1.6 g / ml, 1.7 g / ml, 1.8 g / ml, 1.9 g / ml, 2.0 g / ml or a range consisting of any two numbers therein.
[0040] S2) the oxide Me containing the doping element Me m O n , lithium salt and precursor are mixed and calcined to obtain a core layer. Specifically, the mixture is stirred at 2000 rpm to 3000 rpm in a high-speed mixer for 10 min to 30 min, and then the mixture is calcined to obtain the core layer.
[0041] In some embodiments, the oxide Me doped with the element Me m O n The molar ratio of Me in the lithium salt, Li in the lithium salt and the sum of the amounts of metal elements Ni and Mn in the precursor is Me:Li:(Ni+Mn)=(0.002~0.006):(1.05~1.25):1.
[0042] In some embodiments, the calcination temperature is 800° C. to 1100° C., the calcination time is 8 h to 15 h, and the calcination atmosphere is oxygen or air.
[0043] In some embodiments, Me m O n In the formula, m is 1 or 2 or 3, n is 1 or 2 or 3, Me m O n At least one selected from Al2O3, B2O3, ZrO2, TiO2, WO3, SrO, MgO, CeO2, Y2O3. Preferably, it is nano ZrO2, and the median particle size D50 of nano ZrO2 is ≤50nm.
[0044] In some embodiments, the lithium salt is lithium hydroxide or lithium carbonate, and the molar ratio of the lithium element in the lithium salt to the sum of the amount of nickel and manganese in the precursor is 1.05≤Li / (Ni+Mn)≤1.25. Specifically, the value of Li / (Ni+Mn) can be 1.05, 1.08, 1.1, 1.12, 1.15, 1.18, 1.2, 1.22, 1.25 or a range consisting of any two numbers therein. During the preparation of the core layer, an excess of lithium is added so that the lithium ions can be fully embedded in the layered structure to form a stable cobalt-free layered structure.
[0045] S3) The core layer obtained in step S2) is crushed and sieved, and the total alkali of the core layer is tested. The amount of nickel source and tellurium source added is calculated according to the total alkali test result, and the nickel source and tellurium source are added, and LaB6 is added. The mixture is stirred at 1000rpm to 2000rpm in a high-speed mixer for 10min to 20min, and then calcined to obtain a finished positive electrode material.
[0046] In some embodiments, the nickel source includes at least one of nickel oxide, nickel oxide, nickel sulfate, nickel nitrate, and nickel chloride, preferably nickel oxide NiO.
[0047] In some embodiments, the nickel source has a median particle size D50 ≤ 100 nm.
[0048] In some embodiments, the tellurium source is tellurium dioxide TeO 2 .
[0049] In some embodiments, the median particle size D50 of the tellurium source is ≤ 100 nm.
[0050] In some embodiments, the median particle size D50 of LaB6 is ≤100 nm.
[0051] When the median particle size of the nickel source, tellurium source and LaB6 is within the above range, the particle size of the nickel source, tellurium source and LaB6 can be controlled within a reasonable range, so that the nickel source, tellurium source and LaB6 are fully mixed with the core layer obtained in step S2), ensuring the calcination effect, so that the coating layer formed by the nickel source, tellurium source and LaB6 fully covers the core layer.
[0052] In some embodiments, the mass of LaB6 is the oxide Me doped with element Me. m O n , lithium salt and precursor total mass. Specifically, LaB6 can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5% of the core layer mass or a range consisting of any two numbers therein.
[0053] Among them, the full alkali test method of the core layer includes the following steps:
[0054] The core layer was dispersed in deionized water, stirred and dispersed for at least 30 minutes, and filtered to obtain the supernatant. The supernatant was titrated with calibrated dilute hydrochloric acid, and phenolphthalein and methyl orange were used as indicators of the titration end points, respectively. Two titration end points were obtained, and the content of LiOH a and the content of Li2CO3 b were calculated. The mass ratio of the core layer mass, the amount of nickel source added, and the amount of tellurium source added was:
[0055] Core layer quality: nickel source addition amount: tellurium source addition amount = 1: [(a / 23.95+b / 73.87)×74.7]:
[0056] The following is a description of the preparation method of the positive electrode material provided in the present application in conjunction with specific embodiments:
[0057] Example 1
[0058] S1) uses cobalt-free cathode precursor Ni 0.55 Mn 0.45 (OH)2, median particle size D50 is 3.5um, specific surface area is 19.5m 2 / g, and the tap density is 1.7g / ml.
[0059] S2) Ni 0.55 Mn 0.45 (OH)2, Li2CO3, and ZrO2 were mixed at a high speed in a mass ratio of 100:46.67:0.29, stirred at 2000 rpm for 20 min, and the mixed materials were calcined at 1000°C for 10 h in an air atmosphere, cooled, crushed, and sieved to obtain a core layer.
[0060] Among them, the median particle size D50 of ZrO2 is 25nm.
[0061] S3) The total alkali of the core layer was tested, and the results showed that the content of LiOH a was 0.38%, and the content of Li2CO3 b was 1.36%. By calculation, the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 were mixed at a mass ratio of 100:2.56:2.74:0.2, stirred at 1500rpm for 15min, and the mixed material was calcined in an oxygen atmosphere at a calcination temperature of 800℃ and a calcination time of 12h to obtain the positive electrode material Li 1.15 Ni 0.55 Mn 0.446 Zr 0.004 O2@Li2Ni2TeO6 / LaB6.
[0062] Among them, the median particle size D50 of nano-NiO is 56nm, the median particle size D50 of nano-TeO2 is 78nm, and the median particle size D50 of nano-LaB6 is 69nm.
[0063] The positive electrode material prepared in this example was added to N-methylpyrrolidone (NMP) at a mass ratio of 92:4:4 with carbon black (SP) and polyvinylidene fluoride (PVDF), mixed evenly and coated on aluminum foil, dried at 100°C for 4 h, cut into positive electrode sheets with a diameter of 12 mm, assembled into button half-cells, left to stand for 12 h, and subjected to electrochemical testing.
[0064] Embodiment 2:
[0065] S1) uses cobalt-free cathode precursor Ni 0.65 Mn 0.35(OH)2, median particle size D50 is 3.9um, specific surface area is 22.3m 2 / g, and the tap density is 1.5g / ml.
[0066] S2) Ni 0.65 Mn 0.35 (OH)2, LiOH and ZrO2 were mixed at a high speed in a mass ratio of 100:85.22:0.29 and stirred at 2500 rpm for 15 min. The mixed materials were calcined at 950°C for 12 h in an air atmosphere, cooled, crushed and sieved to obtain a core layer.
[0067] Among them, the median particle size D50 of ZrO2 is 25nm.
[0068] S3) The total alkali of the core layer was tested, and the results showed that the LiOH content a was 0.45%, and the Li2CO3 content b was 1.43%. By calculation, the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 were mixed at a mass ratio of 100:2.85:3.04:0.2, stirred at 1500rpm for 15min, and the mixed material was calcined in an oxygen atmosphere at a calcination temperature of 800℃ and a calcination time of 12h to obtain the positive electrode material Li 1.1 Ni 0.65 Mn 0.346 Zr 0.004 O2@Li2Ni2TeO6 / LaB6.
[0069] Among them, the median particle size D50 of nano-NiO is 56nm, the median particle size D50 of nano-TeO2 is 78nm, and the median particle size D50 of nano-LaB6 is 69nm.
[0070] The positive electrode material prepared in this example was added to N-methylpyrrolidone (NMP) at a mass ratio of 92:4:4 with carbon black (SP) and polyvinylidene fluoride (PVDF), mixed evenly and coated on aluminum foil, dried at 100°C for 4 h, cut into positive electrode sheets with a diameter of 12 mm, assembled into button half-cells, left to stand for 12 h, and subjected to electrochemical testing.
[0071] Example 3
[0072] S1) uses cobalt-free cathode precursor Ni 0.95 Mn 0.05 (OH)2, median particle size D50 is 4.2um, specific surface area is 13.9m 2 / g, and the tap density is 1.4g / ml.
[0073] S2) Ni 0.95 Mn 0.05(OH)2, LiOH and ZrO2 were mixed at a high speed in a mass ratio of 100:95.66:0.29 and stirred at 3000 rpm for 10 min. The mixed materials were calcined at 800°C for 15 h in an air atmosphere, cooled, crushed and sieved to obtain a cobalt-free layered positive electrode material.
[0074] Among them, the median particle size D50 of ZrO2 is 25nm.
[0075] S3) The total alkali content of the core layer was tested, and the results showed that the LiOH content a was 0.52%, and the Li2CO3 content b was 1.56%. By calculation, the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 were mixed at a mass ratio of 100:3.2:3.42:0.5, stirred at 1500rpm for 15min, and the mixed material was calcined in an oxygen atmosphere at a calcination temperature of 800℃ and a calcination time of 12h to obtain the positive electrode material Li 1.25 Ni 0.95 Mn 0.046 Zr 0.004 O2@Li2Ni2TeO6 / LaB6.
[0076] Among them, the median particle size D50 of nano-NiO is 56nm, the median particle size D50 of nano-TeO2 is 78nm, and the median particle size D50 of nano-LaB6 is 69nm.
[0077] The positive electrode material prepared in this example was added to N-methylpyrrolidone (NMP) at a mass ratio of 92:4:4 with carbon black (SP) and polyvinylidene fluoride (PVDF), mixed evenly and coated on aluminum foil, dried at 100°C for 4 h, cut into positive electrode sheets with a diameter of 12 mm, assembled into button half-cells, left to stand for 12 h, and subjected to electrochemical testing.
[0078] Example 4
[0079] The positive electrode material was prepared according to the preparation method provided in Example 1 and assembled into a button half-cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0080] In step S1), the cobalt-free cathode precursor Ni 0.60 Mn 0.40 (OH)2, step S2) Ni 0.60 Mn 0.40 (OH)2, LiOH, and ZrO2 are mixed at a high speed in a mass ratio of 100:60.44:0.29. In step S3), the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 are mixed in a mass ratio of 100:2.72:2.86:0.2.
[0081] Example 5
[0082] The positive electrode material was prepared according to the preparation method provided in Example 1 and assembled into a button half-cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0083] In step S1), the cobalt-free cathode precursor Ni 0.75 Mn 0.25 (OH)2, step S2) Ni 0.75 Mn 0.25 (OH)2, LiOH, and ZrO2 are mixed at a high speed in a mass ratio of 100:88.34:0.29. In step S3), the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 are mixed in a mass ratio of 100:3.02:3.14:0.2.
[0084] Example 6
[0085] The positive electrode material was prepared according to the preparation method provided in Example 1 and assembled into a button half-cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0086] In step S1), the cobalt-free cathode precursor Ni 0:80 Mn 0.20 (OH)2, step S2) Ni 0:80 Mn 0.20 (OH)2, LiOH, and ZrO2 are mixed at a high speed in a mass ratio of 100:90.36:0.29. In step S3), the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 are mixed in a mass ratio of 100:3.05:3.26:0.2.
[0087] Example 7
[0088] The positive electrode material was prepared according to the preparation method provided in Example 1 and assembled into a button half-cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0089] In step S1), the cobalt-free cathode precursor Ni 0.85 Mn 0.15 (OH)2, step S2) Ni 0.85 Mn 0.15 (OH)2, LiOH, and ZrO2 are mixed at a high speed in a mass ratio of 100:92.64:0.29. In step S3), the obtained core layer, nano-NiO, nano-TeO2, and nano-LaB6 are mixed in a mass ratio of 100:3.16:3.38:0.5.
[0090] Comparative Example 1
[0091] S1) uses cobalt-free cathode precursor Ni 0.55 Mn 0.45 (OH)2, median particle size D50 is 3.5um, specific surface area is 19.5m 2 / g, and the tap density is 1.7g / ml.
[0092] S2) Ni 0.55 Mn 0.45 (OH)2, Li2CO3, and ZrO2 were mixed at a high speed in a mass ratio of 100:46.67:0.29, stirred at 2000 rpm for 20 min, and the mixed materials were calcined at 1000°C for 10 h in an air atmosphere, cooled, crushed, and sieved to obtain a core layer.
[0093] Among them, the median particle size D50 of ZrO2 is 25nm.
[0094] S3) The core layer and nano-Al2O3 are mixed at a mass ratio of 100:0.29, stirred at 1500 rpm for 15 min, and the mixture is calcined in an oxygen atmosphere at a calcination temperature of 700°C for 5 h to obtain the positive electrode material Li 1.1 Ni 0.55 Mn 0.446 Zr 0.004 O2@Al2O3.
[0095] The positive electrode material prepared in Comparative Example 1, carbon black (SP) and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) in a mass ratio of 92:4:4, mixed evenly and coated on aluminum foil, dried at 100°C for 4 h, cut into positive electrode sheets with a diameter of 12 mm, assembled into button half-cells, left to stand for 12 h, and subjected to electrochemical testing.
[0096] Comparative Example 2:
[0097] The positive electrode material was prepared according to the method of Example 1 and assembled into a button cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0098] The coating layer does not include LaB6, and the positive electrode material Li 1.15 Ni 0.55 Mn 0.446 Zr 0.004 O2@Li2Ni2TeO6.
[0099] Comparative Example 3:
[0100] The positive electrode material was prepared according to the method of Example 1 and assembled into a button cell for electrochemical testing, except for the following differences, the rest was the same as Example 1:
[0101] The coating layer does not include Li2Ni2TeO6, but only includes LaB6, and the positive electrode material Li 1.15 Ni 0.55 Mn 0.446 Zr 0.004 O2@LaB6.
[0102] Electrochemical testing:
[0103] The button cells assembled from Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to electrochemical tests respectively, and the test methods are as follows:
[0104] DCR test steps at low temperature and 100% SOC:
[0105] Charge at a rate of 0.1C in a 25℃ oven until the voltage reaches 4.3V~4.5V, and record every 10s; charge at a constant voltage of 4.3V~4.5V until the rate reaches 0.02C, and record every 10s; adjust the oven to -20℃, let it stand for 180 minutes, record every 10s, record the cut-off voltage V1, then discharge at 0.1C for 10s, record every 0.1s, and record the voltage V2 at the end of 10s.
[0106] Then, DCR at 100% SOC = (V1-V2) / I 0.1C .
[0107] Full alkali test:
[0108] The positive electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were respectively dispersed in deionized water, stirred and dispersed for at least 30 minutes, filtered to obtain a supernatant, and the supernatant was subjected to acid-base titration with calibrated dilute hydrochloric acid, using phenolphthalein and methyl orange as indicators of the titration end points, respectively, to obtain two titration end points, and the content of LiOH and the content of Li2CO3 in the positive electrode material were calculated.
[0109] The full alkali test results, cycle, capacity, rate and low temperature DCR data of the positive electrode materials obtained in Examples 1 to 7 of the present invention and Comparative Examples 1 to 3 are shown in Table 1.
[0110] Table 1
[0111]
[0112]
[0113] As shown in Table 1, the positive electrode materials of the core layer-coating layer structure prepared in Examples 1 to 7 are coated with a layer of nano-Li2Ni2TeO6, which consumes the excess lithium applicable in the core layer, so that the total alkali of the positive electrode material is significantly reduced. Comparative Example 1 uses nano-Al2O3 as the coating layer, the coating layer of Comparative Example 2 contains only Li2Ni2TeO6, but does not include LaB6, and the coating layer of the positive electrode material provided in Comparative Example 3 does not include Li2Ni2TeO6, but only includes LaB6, resulting in the 4C / 1C cycle life and 50-week cycle retention rate of the button battery formed by the positive electrode materials prepared in Comparative Examples 1 to 3 being lower than the button battery formed by the positive electrode materials provided in Examples 1 to 7, and the DCR of the button battery formed by the positive electrode materials prepared in Comparative Examples 1 to 3 at -20°C is significantly higher than that of the button battery formed by the positive electrode materials provided in Examples 1 to 7, indicating that the button battery formed by the positive electrode materials prepared in Comparative Examples 1 to 3 generates more heat, thereby affecting the safety performance of the lithium-ion battery when in use.
[0114] The above is a detailed introduction to a positive electrode material, a preparation method thereof and a lithium-ion battery provided in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A positive electrode material, characterized in that: It comprises a core layer and a coating layer arranged on the surface of the core layer; The general formula of the core layer includes LiNi x Mn y Me z O2, wherein 0.5<x<1, x+y+z=1, and Me is at least one selected from the group consisting of Zr, Sr, W, Al, Ti, Mg, Ce, Y, and B; The coating layer includes Li2Ni2TeO6 and LaB6.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material is a layered positive electrode material, and the median particle size D50 of the positive electrode material is 2 to 4 μm.
3. The positive electrode material according to claim 1, characterized in that The specific surface area of the positive electrode material is 0.3 to 0.8 g / cm 2 The tap density of the positive electrode material is 1.6 to 2.0 g / ml.
4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: Provide a precursor, the molecular formula of which includes Ni a Mn b (OH)2, where 0.5<a<1, a+b=1; The oxide Me containing the doping element Me m O n , lithium salt and the precursor are mixed and calcined to obtain a core layer; The core layer is crushed and sieved, a nickel source and a tellurium source are added, and LaB6 is added, and the mixture is mixed and calcined to obtain the positive electrode material.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: The oxide of the doping element Me m O n The molar ratio of Me in the lithium salt, Li in the lithium salt and the sum of the amounts of metal elements Ni and Mn in the precursor is Me:Li:(Ni+Mn)=(0.002-0.006):(1.05-1.25):
1.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: The median particle size D50 of the precursor is 2.5 μm to 4.5 μm, and the specific surface area is 10 g / cm 2 ~25g / cm 2 , the tap density is 1.2g / ml~2.0g / ml.
7. The method for preparing the positive electrode material according to claim 4, characterized in that: Oxide doped with element Me m O n The median particle size D50 is ≤50 nm, and the molar ratio of the lithium element in the lithium salt to the sum of the amounts of nickel and manganese in the precursor is 1.05≤Li / (Ni+Mn)≤1.
25.
8. The method for preparing the positive electrode material according to claim 4, characterized in that: The nickel source is nickel oxide; the tellurium source is tellurium dioxide; The median particle size D50 of the nickel source is ≤100nm, the median particle size D50 of the tellurium source is ≤100nm, and the median particle size D50 of the LaB6 is ≤100nm; The mass of LaB6 is the oxide of the doping element Me m O n , lithium salt and 0.1% to 0.5% of the total mass of the precursor; The Me m O n wherein m is 1 or 2 or 3, n is 1 or 2 or 3, and Me m O n At least one selected from Al2O3, B2O3, ZrO2, TiO2, WO3, SrO, MgO, CeO2, and Y2O3.
9. The method for preparing the positive electrode material according to claim 4, characterized in that: The full alkali test of the core layer is performed, and the addition amount of the nickel source and the tellurium source is calculated according to the full alkali test result. The full alkali test method of the core layer comprises the following steps: The core layer is dispersed in deionized water, stirred and filtered to obtain a supernatant, and the supernatant is titrated, using phenolphthalein and methyl orange as indicators of the titration end point, respectively, to obtain two titration end points, and the content a of LiOH and the content b of Li2CO3 are calculated; The mass ratio of the core layer mass, the nickel source addition amount and the tellurium source addition amount is: Core layer quality: nickel source addition amount: tellurium source addition amount = 1: [(a / 23.95+b / 73.87)×74.7]:
10. A lithium ion battery, characterized in that: The invention comprises the positive electrode material as claimed in any one of claims 1 to 3 or the positive electrode material prepared by the preparation method of the positive electrode material as claimed in any one of claims 4 to 9.
Citation Information
Patent Citations
Metallate electrodes
CN109980222A
Inorganic / organic composite solid electrolyte and preparation method and application thereof
CN112909324A